Adolescent substance use and subsequent personality disorder : Findings from the 1986 Northern Finland Birth Cohort Study - Gyursánszky, Alex (My University, 2025)
Purpose There is a lack of longitudinal research covering the association between adolescent substance use and subsequent personality disorder (PD) in later adulthood. Most of the studies in this field are small numbered with short follow-up periods. We study this association utilizing a large general population-based sample with prospective data. Methods The Northern Finland Birth Cohort 1986 (n=7744) with linkage to nationwide register data was used to study the association of self-reported alcohol use, lifetime use of cannabis, other illicit drugs, prescription drugs and inhalants by age 15/16 years with PD diagnoses by age 33. Cox regression analysis with Hazard Ratios (HR) and 95% confidence intervals (CI) was used. Sex, family structure, maternal and paternal education and any psychiatric diagnosis by age 15/16 were considered as confounders. Results During follow up, 174 (2.2%) of the 7,744 participants were diagnosed with any PD, the most common of which was BPD (48.3% of all PD; n=86). When taking into account psychiatric diagnoses before age 15/16, family structure and other substance use than the substance variable under consideration, the association remained for the following variables: AFI ≤12 years or younger (HR 2.2; 95% CI 1.1-4.3), lifetime cannabis use by age 15/16 (HR 3.8; 95% CI 1.5-9.9) and lifetime use of prescription drugs by age 15/16 (HR 1.9; 95% CI 1.2-3.1). Discussion In this study, adolescent substance use associated with increased risk for subsequent PD diagnosis. These findings emphasize prevention, early detection and interventions for adolescent substance use.
Keywords: adolescent, substance use, personality disorder